EFEKTIVITAS PENGEMBANGAN BAHAN AJAR BERBASIS BUKU CERITA DI ERA NEW NORMAL PADA MATA PELAJARAN SKI TEMA MENELADANI PERJUANGAN DAKWAH RASULULLAH SAW. DI MADINAH - Moh Hafid; Agus Fauzi (Fakultas Tarbiyah, Universitas Ibrahimy, 2022)
This research aimed to determine the effectiveness of immplementation teaching material based buku cerita on the Islamic culture history subject with theme the imitating the prophet Muhammad’s dakwah struggle in Madina in the new normal era. The subjects of this study were students of grade 10th in Argayasa Islamic Senior High School. This study uses experimental research methods with the research design used postest only control design. Test instrument was given to student is multiple choice questions consisting of 10 questions. Data analyses uses different test mann-whitney in nonparametric statistic. The result showed that average value of experimental and control classes, respectively 35,62 and 13,38. Furthermore, using mann-whitney that shows the value of Asymp. Sig. (2-tailed) is 0,000. So that there is significantly effect by a treatment of learning material based storybook to student learning achievement on the Islamic culture history subject with theme the imitating the prophet Muhammad’s dakwah struggle in Madina. So, learning material based storybook is effective used on the Islamic culture history subject with theme the imitating the prophet Muhammad’s dakwah struggle in Madina.